1974
DOI: 10.1111/j.1471-4159.1974.tb11585.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of S‐100 Protein

Abstract: S-100 protein has been found in the nuclei isolated from the brain cortex of rabbit. The nuclear S-100 constitutes a small portion (0.55 per cent) of the S-100 present in the cytosol. Most of the large and pale nuclei appear to contain much more S-100 than the small and dark ones. The nuclear membrane is permeable in vitro to $100 in presence of divalent cations. Three forms of S-100 occur in subnuclear fractions: free S-100, present in the soluble protein fraction; labile-bound S-100, present in the deoxyribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
5
1

Year Published

1976
1976
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(11 citation statements)
references
References 39 publications
5
5
1
Order By: Relevance
“…Most of it was localized to the neuronal nuclear membrane and the nucleoplasm while the nucleolus lacked significant S-100 activity. This nuclear localization is in general agreement with the results of Michetti et al (30), although we could not reproduce the specific nucleolar enrichment of S-100 reported by these authors.…”
Section: Subcellular Distribution Of the S-100 Proteinsupporting
confidence: 94%
“…Most of it was localized to the neuronal nuclear membrane and the nucleoplasm while the nucleolus lacked significant S-100 activity. This nuclear localization is in general agreement with the results of Michetti et al (30), although we could not reproduce the specific nucleolar enrichment of S-100 reported by these authors.…”
Section: Subcellular Distribution Of the S-100 Proteinsupporting
confidence: 94%
“…8-10). The lack of detection of SI00 protein in neu ronal cell nuclei is at variance with those reports on the presence of S100 protein in brain cell nuclei based on immunohistochemi cal experiments carried out not only on tissue sections [28], but also on isolated neurones [15,16] and isolated brain cell nuclei [22], We have attempted to detect, by inimunohistochemistry, S100 protein in isolated fixed and unfixed brain cell nuclei. Control experi ments showed that endogenous peroxidase activity is absent from brain cell nuclei as shown by direct incubation of either tissue sections or of isolated nuclei with DAB and H.,02 under the appropriate conditions.…”
Section: S I00 Protein and Cell Nucleicontrasting
confidence: 46%
“…The most likely explanation of the claimed presence of S100 protein in neuronal nuclei detected by immunofluorescence [15,22] and even by complement fixation [22] is that it results from erroneous interpretation of the non-specific adsorption of Ig by isolated nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…S-100 was electrochemically iodinated by the method of ROSA et al (1964). As verified earlier (MICHETTI et al, 1974), 1251-labelled S-100 conserves the immunological and electrophoretic properties of native S-100. 12SI-labelled S-100 had a mean specific activity of 1 mCi/mg protein.…”
supporting
confidence: 76%